Local Application of a Gentamicin-Loaded Hydrogel Early After Injury Is Superior to Perioperative Systemic Prophylaxis in a Rabbit Open Fracture Model. Issue 5 (May 2020) - Vallejo Diaz, Alejandro; Deimling, Christian; Morgenstern, Mario; D'Este, Matteo; Puetzler, Jan; Zeiter, Stephan; Arens, Daniel; Metsemakers, Willem-Jan; Richards, R. Geoff; Eglin, David; Moriarty, T. Fintan
Abstract : Objectives: Open fractures are at significant risk of developing a fracture-related infection, despite the routine administration of perioperative antibiotic prophylaxis. Early application of antibiotic prophylaxis is known to reduce infection rates; however, most international guidelines focus on postoperative duration rather than prehospital administration. We compared conventional perioperative prophylaxis against early prehospital prophylaxis either as a systemic single shot of cefuroxime or a locally applied gentamicin-loaded hydrogel in a laboratory animal model. Methods: Thirty New Zealand white rabbits underwent a first surgical procedure to create an open wound, bone damage and contamination with Staphylococcus aureus. After a 4-hour observation period mimicking the time-to-treatment, the animals underwent a second procedure to irrigate the wound and apply a fracture fixation device. The 5 groups (n = 6 per group) received (1) no treatment; (2) conventional 24-hour cefuroxime; (3) an early single shot of cefuroxime 15 minutes after trauma; (4) a combined early and standard systemic prophylaxis; and (5) early application of a gentamicin-loaded hydrogel that was removed during irrigation. Results: Untreated animals displayed high numbers of bacteria in irrigation fluid and were all highly culture positive at euthanasia. Three of 6 animals were culture positive at euthanasia after conventional prophylaxis. Early systemic prophylaxis reduced bacterial burden in irrigation fluid by up to 100-fold, but 5/6 animals were culture positive at euthanasia. The combined prophylaxis displayed greater efficacy with only 1/6 rabbits culture positive at euthanasia. Local application of the gentamicin-loaded hydrogel reduced bacteria recovered by irrigation to just above our detection limit, and at euthanasia, all animals were culture negative at euthanasia. Conclusions: Early systemic antibiotic administration can significantly reduce bacterial burden in the operative field and reduce culture positivity at euthanasia when continued for 24 hours after injury. The early application of a gentamicin-loaded hydrogel that was removed during irrigation displayed superior efficacy to early systemic therapy alone and postoperative conventional gold standard 24-hour systemic therapy alone. These experimental results highlight the importance of early antibiotic administration in fracture care.